Expansion and Delivery of Human Chondrocytes on Gelatin-Based Cell Carriers - Krishi Patel; Derya Ozhava; Yong Mao (Gels)
Cartilage damage is common in sports injuries and cartilage-related diseases, such as degenerative joint and rheumatic disorders. Autologous chondrocyte implantation (ACI) is a widely used cell-based therapy for repairing cartilage damage in clinical practice. In this procedure, a patient’s chondrocytes are isolated, cultured in vitro to expand the cell population, and then implanted into the damaged site. However, in vitro expansion of chondrocytes on standard 2D culture surfaces leads to dedifferentiation (loss of the chondrocyte phenotype), and the delivery of detached cells has proven to be ineffective. To overcome these limitations, the matrix-assisted ACI (MACI) procedure was developed. In MACI, matrices such as hydrogels and microspheres are used as cell carriers or scaffolds to deliver expanded chondrocytes, enhancing cell viability and precision delivery. To streamline the two key steps of MACI—cell expansion and delivery—this study aims to investigate various configurations of gelatin-based hydrogels for their potential to support both cell expansion and delivery as a single step. This study evaluated gelatin microspheres (Gel MS), micronized photo-crosslinked GelMA microparticles (GelMA MP), and bulky GelMA hydrogels containing cells (GelMA HG). Cell growth, maintenance of the chondrocyte phenotype, and cartilage extracellular matrix (ECM) production were assessed in pellet cultures for cells grown on/in these carriers, compared with cells cultured on tissue culture-treated polystyrene (TCP). Our results demonstrate that normal human knee articular chondrocytes exhibit robust growth on Gel MS and form aggregates enriched with glycosaminoglycan-rich ECM. Gel MS outperformed both GelMA MP and GelMA HG as a cell carrier by both supporting long-term cell growth with reduced dedifferentiation and precision delivery.